Analisis Kebijakan SPNF- SKB Kota Medan (Jurnal Insan Pendidikan dan Sosial Humaniora, 2025)
This research aims to analyze the policies implemented by SPNF-SKB Medan City in providing non-formal education for the community. This institution plays an important role in providing equal access to education, skills training and socio-cultural development. This research uses a descriptive method with a qualitative approach involving interviews and field observations. The research results show that the programs held at SPNF-SKB Medan City, such as Packages A, B, and C, have contributed greatly to improving the education of people who do not have access to formal education. Apart from that, the skills training provided is able to improve people's abilities in the world of work and entrepreneurship. However, budget constraints are the main challenge in developing this educational service. This research suggests the need for further support from the government and collaboration with other institutions to overcome these barriers and expand the reach of non-formal education services.